A method for processing inertial measurement unit data for para-Nordic sit-ski race analysis: a step-by-step guide - Severin, A. C.; Ettema, G.; Kocbach, J. (Sports Engineering, 2025)
Inertial measurement units can provide biomechanical insights into tasks performed in the laboratory and in the field and have yielded valuable information for practitioners and researchers alike within several sports. However, for data from such sensors to be interpretable, it requires considerable processing. Although the literature using sensor technology is substantial, description of the data processing methodologies often lacks sufficient detail to allow for replication and therefore limits applications in the field and research. To address these limitations in the existing literature, we present a step-by-step approach to process the data from a single inertial measurement unit aggregated with global navigation satellite systems data for performance analysis of the skiing component of an elite-level sitting para-biathlon competition. Since the degree of trunk motion is important for sit-ski performance, our analysis extends on previously reported frameworks and aims at adding new quantifications of trunk range of motion in addition to speed, cycle rate, and cycle length. This new framework will allow analysis of how all these important variables changes throughout the racecourse. In addition, we discuss the rationale behind the design of the method along with its limitations and underline processing options that can be adapted to suit a variety of research questions or analytical approaches, which may include other activities or measurement devices. With this, we encourage other researchers to report their methodology in detail and, by extension, contribute to facilitating the process of replicating and developing existing methods for both academia and practice.